THE EFFECT OF PROFESSIONAL COMPETENCE AND TEACHER SELF-EFFICACY MODERATED SCHOOL CULTURE ON CLASS MANAGEMENT - Ani Hidayatul Mai’yah; Sunarto Sunarto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
The background of this research is that classroom management is an integral part of effective learning. The results of the need assessment for classroom management in schools have not reached the management standards according to the Minister of Education and Culture Number 22 of 2016. Teachers in managing classes require professional competence and teacher efficacy. The purpose of this study was to analyze the effect of professional competence and teacher self-efficacy on classroom management. Quantitative research methods are used in this study. The data analysis technique used moderation regression analysis with pure moderator type with interaction techniques. The results of the model test analysis show that professional competence has a positive effect on classroom management, and teacher self-efficacy does not affect classroom management. The conclusion of this study is that teacher competence has an influence on classroom management, and teacher self-efficacy does not affect classroom management Keywords: classroom management, professional competence, and teacher self-efficacy